Allspice and Clove As Source of Triterpene Acids Activating the G Protein-Coupled Bile Acid Receptor TGR5 - Ladurner, Angela; Zehl, Martin; Grienke, Ulrike; Hofstadler, Christoph; Faur, Nadina; Pereira, Fátima C.; Berry, David; Dirsch, Verena M.; Rollinger, Judith M. (Frontiers in Pharmacology, 2017)
Worldwide, metabolic diseases such as obesity and type 2 diabetes have reached epidemic proportions. A major regulator of metabolic processes that gained interest in recent years is the bile acid receptor TGR5. This G-protein coupled membrane receptor can be found predominantly in the intestine, where it is mainly responsible for the secretion of the incretins glucagon-like peptide 1 (GLP-1) and peptide YY (PYY). The aim of this study was i) to identify plant extracts with TGR5-activating potential, ii) to narrow down their activity to the responsible constituents, and iii) to assess whether the intestinal microbiota produces transformed metabolites with a different activity profile. Chenodeoxycholic acid (CDCA) served as positive control for both, the applied cell-based luciferase reporter gene assay for TGR5 activity and the biotransformation assay using mouse fecal slurry. The suitability of the workflow was demonstrated by the biotransformation of CDCA to lithocholic acid (LCA) resulting in a distinct increase in TGR5 activity. Based on a traditional Tibetan formula, nineteen plant extracts were selected and investigated for TGR5 activation. Extracts from the commonly used spices Syzygium aromaticum (SaroE, clove), Pimenta dioica (PdioE, allspice), and Kaempferia galanga (KgalE, aromatic ginger) significantly increased TGR5 activity. After biotransformation, only KgalE showed significant differences in its metabolite profile, which however did not alter its TGR5 activity compared to non-transformed KgalE. UHPLC-HRMS analysis revealed triterpene acids (TTAs) as the main constituents of the extracts SaroE and PdioE. Identification and quantification of TTAs in these two extracts as well as comparison of their TGR5 activity with reconstituted TTA mixtures allowed the attribution of the TGR5 activity to TTAs. EC50s were determined for the main TTAs, i.e. oleanolic acid (2.2 ± 1.6 µM), ursolic acid (1.1 ± 0.2 µM), as well as for the hitherto unknown TGR5 activators corosolic acid (0.5 ± 1.0 µM) and maslinic acid (3.7 ± 0.7 µM). In conclusion, extracts of clove, allspice, and aromatic ginger activate TGR5, which might play a pivotal role in their therapeutic use for the treatment of metabolic diseases. Moreover, the TGR5 activation of SaroE and PdioE could be pinpointed solely to TTAs.